Eliciting permanent and transitory undeclared work from matched administrative and survey data - Péter Elek; János Köllő (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2016)
We study the undeclared work patterns of Hungarian employees in relatively stable jobs, using a panel dataset that matches individual-level self-reported Labour Force Survey (LFS) data with administrative data from the Pension Directorate for 2001-2006. We estimate the determinants of undeclared work using Heckman-type random-effects panel probit models, and develop a two-regime model to separate permanent and transitory undeclared work, where the latter follows a Markov chain. We find that about 6 per cent of workers went permanently unreported for six consecutive years, and a further 3-4 per cent were transitorily unreported in any given year. By simulating the permanent and transitory components of undeclared work, we examine the implications for health and pension eligibility.
Keywords: C23; C25; H26; J46; 330; undeclared work; labour input method; matched administrative-survey data; random-effects panel probit model with endogenous selection; Markov chain